Prioritizing Young Western White Pine Stands for Blister Rust Pruning on the Warm Springs Reservation. Issue 5 (12th January 2017) - Singleton, Ryan; Oblinger, Brent W.
Abstract : A prioritization protocol was developed on the Confederated Tribes of Warm Springs Reservation of Oregon to inventory and identify stands with young western white pine ( Pinus monticola ) for management of white pine blister rust (caused by Cronartium ribicola ) by pruning. Pruning lower branches on young white pines has been shown to be effective in parts of the Northwest for prevention and suppression of blister rust. Analysis of current inventory and light detection and ranging (LiDAR) data was completed to identify stands based on the abundance and height of white pine present. Once a list of candidate stands was generated, a field-based inventory of those stands was completed to determine blister rust infection levels. Data from the surveys were analyzed, and a decision tree was used to prioritize stands for pruning based on the number of prunable white pine present and blister rust infection levels. Spatial trends in current infection levels showed that blister rust was more damaging in the two northern areas than in the southern area included in analysis. Twenty-one stands were designated as being high priority for blister rust pruning. This process could aid other tribes and land managers in the conservation and management of western white pine in the presence of white pine blister rust. Management and Policy Implications The need to conserve and restore five-needle pines in western North America is well documented. In the face of changing climates, overcrowded forests, and blister rust, western white pine requires active management to maintain and improve its presence. From its unique land base and policies favoring active, balanced management, the WSR is well positioned to play a significant role in its conservation. In addition to utilizing a rust resistance genetics program to manage blister rust, one of the few remaining options to combat the disease in young trees is pruning. The WSR has numerous young white pine spread across a large number of plantations without specific knowledge of blister rust infection levels. Rather than indiscriminately choose stands to prune, managers need a systematic approach to determine when and where to prune. The process presented here uses stand-based inventory, LiDAR data, and blister rust survey data to prioritize these stands. In natural resource management, limited budgets necessitate prudent allocation of funding among various projects or treatments. A well-designed, systematic decisionmaking approach will go a long way to applying effective treatments and achieving a good return on investment. This project demonstrated methods for effective prioritization of western white pine pruning projects and could be applied to a variety of project planning efforts in Indian country or other ownerships based on landowner goals, funding levels, and risk tolerance.